To heat or to heal: the uneasy trade-off between energy and healthcare expenditure in Central Asia - Tokhtaeva, Sevara; Khakimov, Obidjon; Eshchanov, Bahtiyor; Magrupov, Aziz (Frontiers in Political Science, 2025)
The influence of housing hazards on healthcare has become a serious problem, considering the past and present implications of international energy laws. In this empirical study, energy poverty was examined to reveal its impact on health-oriented spending in Tajikistan for the year 2013. Our analysis demonstrated the negative effect of fuel poverty on healthcare expenditure across different income groups. The findings indicated that families with high and middle incomes experience a low level of energy poverty, suggesting that the health expenses of households from these income classes are not impacted by energy poverty levels. The low-income group, however, is considered to be fuel-poor, with an energy poverty level prevailing at 10%. Nevertheless, families in the very low-income group live in extreme fuel poverty, spending nearly half of their budget on fuel expenditure. The results provide evidence that fuel poverty negatively affects health and that this effect is deferred, leading to poorer health over time. This paper also investigates the impact of fuel expenditure on healthcare spending, revealing a negative correlation between the two observed variables. The model is controlled for dwelling size, location of housing, and dwelling type, which demonstrate a significant impact on healthcare expenditure. Additionally, household size was found to be highly statistically significant at a 95% confidence interval, holding all other factors constant. Regarding policy, this paper highlights the importance of investments in housing energy schemes to increase efficiency and decrease fuel poverty, thereby improving health indicators. It suggests that conditions in households that reduce fuel poverty can drive down public healthcare costs. The results indicate that the very low and low-income groups experience proportionally higher healthcare expenditure due to fuel poverty, underscoring the necessity for policy intervention.